Decision Support System for Selecting Marching Band Field Commanders Using Profile Matching - Alza, Nurul Hafizhah; Suryamen, Haris (Knowbase : International Journal of Knowledge in Database, 2023)
The selection process for Marching Band field commanders often relies on subjective evaluations such as the coach's feelings or other perceptions that lack objectivity. Therefore, a more systematic and objective approach is required to choose the most suitable marching band field commander. This research aims to establish a Decision Support System using the Profile Matching method. The development methodology employed was the Waterfall model, encompassing five steps: requirements, design, development, testing, and deployment. The research findings revealed three crucial aspects in determining the marching band field commander: body posture, field ability, and personality. Various criteria were utilized, including body language, preparedness, knowledge of marching rules, vocal skills, general understanding of marching bands, accuracy, experience, attitude, and presence. To facilitate the selection process, a decision support system application was developed using the PHP programming language. This system utilizes a database to store processed data and generates output in the form of rankings. The implementation of this decision support system resolves the challenge of determining the best marching band field commander, providing marching bands with a more objective means of identifying the ideal candidate.